Delež dunajskih Čehov pri razvoju bohemistike in slavistike - Honzak-Jahić, Jasna (Slavistična revija, 2005)
The paper outlines the role of Josef Valentin Zlobický (1743-1810) in Vienna at the enf of the 18th century, in the ideological and social circumstances ofthe enlightened absolutism of the Austro-Hungarian monarchy. Zlobický was the first professor of Czech language and literature at the University of Vienna from 1775, the censor of Slavic, mainly Czech publications, and translator of the Josephine Laws.
Keywords: Austria-Hungary; Avstro-Ogrska; biografije; cenzorji; Czech literature; češčina; češka književnost; kulturna zgodovina; prevajalci; profesorji; Zlobický, Josef Valentin, 1743-1810